Insulin-producing cells in the brain of adult Drosophila are regulated by the serotonin 5-HT(1A) receptor. - Luo, J.; Becnel, J.; Nichols, C.D.; Nässel, D.R. (Cellular and molecular life sciences. CMLS, 2012)
Insulin signaling regulates lifespan, reproduction, metabolic homeostasis, and resistance to stress in the adult organism. In Drosophila, there are seven insulin-like peptides (DILP1-7). Three of these (DILP2, 3 and 5) are produced in median neurosecretory cells of the brain, designated IPCs. Previous work has suggested that production or release of DILPs in IPCs can be regulated by a factor secreted from the fat body as well as by neuronal GABA or short neuropeptide F. There is also evidence that serotonergic neurons may regulate IPCs. Here, we investigated mechanisms by which serotonin may regulate the IPCs. We show that the IPCs in adult flies express the 5-HT(1A), but not the 5-HT(1B) or 5-HT(7) receptors, and that processes of serotonergic neurons impinge on the IPC branches. Knockdown of 5-HT(1A) in IPCs by targeted RNA interference (RNAi) leads to increased sensitivity to heat, prolonged recovery after cold knockdown and decreased resistance to starvation. Lipid metabolism is also affected, but no effect on growth was seen. Furthermore, we show that DILP2-immunolevels in IPCs increase after 5-HT(1A) knockdown; this is accentuated by starvation. Heterozygous 5-HT(1A) mutant flies display the same phenotype in all assays, as seen after targeted 5-HT(1A) RNAi, and flies fed the 5-HT(1A) antagonist WAY100635 display reduced lifespan at starvation. Our findings suggest that serotonin acts on brain IPCs via the 5-HT(1A) receptor, thereby affecting their activity and probably insulin signaling. Thus, we have identified a second inhibitory pathway regulating IPC activity in the Drosophila brain.